Retrieval of upper first molar root inadvertently displaced into buccal fat pad during extraction - Mohamed, Ayesha; Domah, Farya; Saund, Daniel (Journal of Case Reports in Dental Medicine, 2025)
Accidental displacement of maxillary teeth or roots perioperatively is well reported, most commonly into the maxillary sinus. We herein report a rare case in which an UL6 retained root was displaced and later retrieved from the buccal fat pad (BFP) under local anaesthesia. The case highlighted the limitations of conventional radiographic examination and the advantages of cone beam computed tomography imaging to aid surgical planning and localise the displaced root.